Cotinine and interferon-gamma levels in pre-school children exposed to household tobacco smoke - Lina Kalalo; Diana Takumansang-Sondakh; Audrey Wahani (Indonesian Pediatric Society, 2013)
Background Environmental tobacco smoke has been consistently linked to negative health outcomes, especially in children, including an increased susceptibility to infections. Cigarette smoking has a depressive effect on interferon-γ (IFN-γ). Serum cotinine is a marker of exposure to smoke.Objective To determine the association between serum cotinine and interferon-γ (IFN-γ) levels in children with household tobacco smoke exposure.Methods We conducted a cross-sectional study at the Tumumpa and Singkil Districts of Manado, Indonesia, from February to May 2012. Subjects were collected by consecutively sampling of healthy children aged 1-3 years who came to the integrated health posts. Seventy-four children were recruited and consisted of two groups of 37 subjects each, the tobacco smoke exposure group and the non-tobacco smoke exposure group. Blood specimens were collected from all subjects for laboratory blood tests of cotinine and IFN-γ levels. Results were analyzed by T-test and Pearson’s correlation analysis with a P<0.05 is considered as statistically significant.Results There was no significant correlation between serum cotinine and interferon-γ levels in the tobacco smoke exposure group. However, the interferon-γ level in the tobacco smoke exposure group was significantly lower than that of the non-tobacco smoke exposure group (P<0.0001).Conclusion Cotinine is not related to the interferon-γ level in children exposed to tobacco smoke, however, the interferon-γ level in children with tobacco smoke exposure is lower than in the non-tobacco smoke exposure group.